Regiocontroled Pd-catalysed C5-arylation of 3-substituted thiophene derivatives using a bromo-substituent as blocking group - Brahim, Mariem; Ben Ammar, Hamed; Soulé, Jean-François; Doucet, Henri (Beilstein Journal of Organic Chemistry, 2016)
The use of a bromo-substituent as blocking group at the C2-position of 3-substituted thiophenes allows the regioselective introduction of aryl substituents at C5-position via Pd-catalysed direct arylation. With 1 mol % of a phosphine-free Pd catalyst, KOAc as the base and DMA as the solvent and various electron-deficient aryl bromides as aryl sources, C5-(hetero)arylated thiophenes were synthesized in moderate to high yields, without cleavage of the thienyl C–Br bond. Moreover, sequential direct thienyl C5-arylation followed by Pd-catalysed direct arylation or Suzuki coupling at the C2-position allows to prepare 2,5-di(hetero)arylated thiophenes bearing two different (hetero)aryl units in only two steps. This method provides a “green” access to arylated thiophene derivatives as it reduces the number of steps to prepare these compounds and also the formation of wastes.
Keywords: aryl bromides; C–H bond activation; catalysis; direct arylation; palladium; thiophenes